2016
DOI: 10.1002/jnr.23759
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 promotes neural proliferation and differentiation and regulates Wnt target gene expression

Abstract: Prostaglandin E2 (PGE2 ) is an endogenous lipid molecule that regulates important physiological functions, including calcium signaling, neuronal plasticity, and immune responses. Exogenous factors such as diet, exposure to immunological agents, toxic chemicals, and drugs can influence PGE2 levels in the developing brain and have been associated with autism disorders. This study seeks to determine whether changes in PGE2 level can alter the behavior of undifferentiated and differentiating neuroectodermal (NE-4C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 90 publications
(116 reference statements)
3
41
0
Order By: Relevance
“…We observed sex‐specific and age‐specific differences that have never been described before in this animal model. The results presented in this study along with published clinical data as well as in vitro and in vivo molecular research strengthen the evidence that abnormal COX2/PGE2 signaling may influence brain development and contribute to ASD pathology. We determined that male and female (COX)‐2 − KI mice lacking activity from the PGE2‐producing enzyme display behaviors linked to autism, specifically in hyperactivity, anxiety, repetitive behaviors, motor strength and social interaction (Table ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We observed sex‐specific and age‐specific differences that have never been described before in this animal model. The results presented in this study along with published clinical data as well as in vitro and in vivo molecular research strengthen the evidence that abnormal COX2/PGE2 signaling may influence brain development and contribute to ASD pathology. We determined that male and female (COX)‐2 − KI mice lacking activity from the PGE2‐producing enzyme display behaviors linked to autism, specifically in hyperactivity, anxiety, repetitive behaviors, motor strength and social interaction (Table ).…”
Section: Discussionsupporting
confidence: 83%
“…Emerging molecular evidence offers insight into possible mechanisms by which abnormal COX2/PGE2 signaling may affect brain development and lead to autism. For example, in vitro studies in our laboratory have shown that elevated levels of PGE2 can modify intracellular calcium dynamics and increase neural proliferation, migration and differentiation in neural stem cells and differentiating neurons . The expression of autism‐linked genes including Ptgs2 , Mmp9 , Ctnnb1 and Wnt3 was also altered as a result of increased PGE2 levels in these model systems .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from VPA, polyunsaturated fatty acids like docosahexaenoic acid, arachidonic acid, linoleic acid, and alpha linolenic acid have been well known to aid in the neural developmental process (Hejr et al, ; Kan, Melamed, Offen, & Green, ; Ma et al, ). Some fatty acid derivatives like Prostaglandin E2 also lead to better neurosphere development and synthesis of mature neural markers in neural stem cells (Wong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HIF-1α is also a key factor in the maintenance of the adult sub-ventricular zone and regulation of NSC biology under hypoxia [16, 18]. Besides, PTGS2 can promote neural proliferation and differentiation and influences Wnt target gene expression [51]. Using the PPI network, module analysis demonstrated that NSC behavior under hypoxia was associated with neuroactive ligand-receptor interaction, chemokine signaling pathway, calcium signaling pathway, and olfactory transduction.…”
Section: Discussionmentioning
confidence: 99%